Letter (copy) : Spanish refugees in France: clothing - Citrine, Walter, 1887-1983
032-0040-001 International. WMC/EAB/AT/943. 7th June, 1939. Mr. W. Schevenels, International Federation of Trade Unions, 9 avenue d'Orsay, Paris, VIIe. Dear Comrade Schevenels, SPANISH REFUGEES IN FRANCE - CLOTHING. You will remember we wrote to you on the 26th May, informing you that a consignment of boots and shoes were being forwarded by the C.W.S. "Progress" to the Federation Syndicale Internationale, Rouen, and asking you to arrange for forwarding instructions from that port. We now desire to arrange some publicity regarding this consignment, with a view to stimulating further gifts of a similar nature, and it would be very useful for as to know whether you have received the goods, and if so, what arrangements have been made for their distribution. We desire to give this information to the press on Friday next, 9th instant, and we would therefore be very grateful if you could let us have your reply by that date. Yours sincerely, General Secretary. 292/946/32/40